1990
DOI: 10.1152/ajpendo.1990.258.5.e813
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow and substrate utilization in insulin-treated diabetic subjects

Abstract: We compared regional cerebral blood flow (rCBF) and arteriojugular vein differences of glucose, ketones, glycerol, lactate, pyruvate, and O2 in eight subjects with well-controlled insulin-dependent diabetes mellitus (IDDM) and in six healthy volunteers. Duration of diabetes was 19.4 +/- 2.1 yr. Measurements were performed before and after 120 min of insulin infusion and concomitant Biostator-controlled normoglycemia. Net uptake of ketones was seen in IDDM subjects before but not after insulin. Net uptake of gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
25
2
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 16 publications
3
25
2
1
Order By: Relevance
“…Samples were also taken at timed intervals to measure the arterial concentrations of ␤-HB, glucose, lactate, glycerol, and insulin, and also to determine hematocrit, pH, and standard bicarbonate concentration. The different concentrations were determined by standard methods, as described by Grill et al (6).…”
Section: Methodsmentioning
confidence: 99%
“…Samples were also taken at timed intervals to measure the arterial concentrations of ␤-HB, glucose, lactate, glycerol, and insulin, and also to determine hematocrit, pH, and standard bicarbonate concentration. The different concentrations were determined by standard methods, as described by Grill et al (6).…”
Section: Methodsmentioning
confidence: 99%
“…Disease variables were either classified as dichotomous variables (e.g., the presence or absence of a history of severe hypoglycemic episodes) or as continuous variables (e.g., duration of diabetes in years). Studies that assessed the (1,3,18,19,20 -32), b ϭ (18,19,22,27,29, c ϭ (6,18,19,25), d ϭ (3,6,18,20,22,23,25,31), e ϭ (6,18,22,25,29), f ϭ (3,6,18,22,25), g ϭ (6,22,25,29), h ϭ (3,22,25), i ϭ (3,6,18,19,21,22,25,30), j ϭ (20,24,28,29,32), k ϭ (20,27), l ϭ (2,3,21,25,29), m ϭ (18,27,29)...…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…Several studies have found that intensively treated patients with type 1 diabetes have cortical metabolic adaptations during hypoglycemia. Positron emission tomography (PET) and arterio-venous difference studies have found that in contrast to control subjects who show a 20 -30% decrease in glucose uptake during moderate hypoglycemia (ϳ2.8 mmol/l), subjects with intensively treated type 1 diabetes show minimal reduction in glucose uptake (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…As early as 1990, Grill et al (7) proposed that this adaptation may largely be due to increased utilization of alternate substrates to glucose, based on the finding that under euglycemic conditions glucose uptake was lower in the subjects with type 1 diabetes. Although glucose is the major substrate supporting metabolism in the central nervous system, under certain conditions, such as starvation, the brain can adapt to use alternative substrates such as ketones and lactate to meet its energy requirements (12)(13)(14).…”
mentioning
confidence: 99%
See 1 more Smart Citation